WEB-BASED GEOGRAPHIC INFORMATION SYSTEM FOR LAMPUNG GIFT STORE - Andi Nurkholis; Yopita Anggela; A Ferico Octaviansyah P (Universitas Teknokrat Indonesia, 2022)
In the face of increasing technological advances, the development of society refers to the ability to keep up with technological developments and the ability to access and present useful information. Lack of information and knowledge about the location of the gift store makes the public or tourists only visit the nearest store or those suggested by friends and people around. This study aims to develop a web-based geographic information system to make it easier for people to find the location of Lampung gift store. In this study using extreme programming as a development method. Based on the results of testing ISO 25010 that has been carried out involving 50 respondents, the conclusion that the quality of the software produced has a success percentage with a total average of 90.66%. So it can be concluded that the percentage value obtained shows the overall software quality has a